People's Republic of China : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that China is transitioning to a new normal, with slower-yet-safer, more sustainable growth. Growth in 2014 fell to 7.4 percent and, in 2015, is forecast to slow further to 6.8 percent on the back of slower investment, especially in real estate. The labor market has remained resilient despite slower growth, as the economy pivots toward the more labor-intensive service sector. Considerable progress has been made in external rebalancing. The current account surplus fell to 2.1 percent in 2014 from the peak of about 10 percent in 2007, and the renminbi has appreciated by about 10 percent since 2014 in real effective terms. Further progress has also been made on domestic rebalancing.